The 5BSL3.2 Functional RNA Domain Connects Distant Regions in the Hepatitis C Virus Genome - Romero-López, Cristina; Berzal-Herranz, Alfredo (Frontiers in Microbiology, 2017)
Viral genomes are complexly folded entities that carry all the information required for the infective cycle. The nucleotide sequence of the RNA virus genome encodes proteins and functional information contained in discrete, highly conserved structural units. These so-called functional RNA domains play essential roles in the progression of infection, which requires their preservation from one generation to the next. Numerous functional RNA domains exist in the genome of the hepatitis C virus (HCV). Among them, the 5BSL3.2 domain in the cis-acting replication element (CRE) at the 3′ end of the viral open reading frame has become of particular interest given its role in HCV RNA replication and as a regulator of viral protein synthesis. These functionalities are achieved via the establishment of a complex network of long-distance RNA–RNA contacts involving (at least as known to date) the highly conserved 3′X tail, the apical loop of domain IIId in the internal ribosome entry site, and/or the so-called Alt region upstream of the CRE. Changing contacts promotes the execution of different stages of the viral cycle. The 5BSL3.2 domain thus operates at the core of a system that governs the progression of HCV infection. This review summarizes our knowledge of the long-range RNA–RNA interaction network in the HCV genome, with special attention paid to the structural and functional consequences derived from the establishment of different contacts. The potential implications of such interactions in switching between the different stages of the viral cycle are discussed.